The Saccadic Re-Centering Bias is Associated with Activity Changes in the Human Superior Colliculus - Krebs, Ruth M.; Schoenfeld, Mircea A.; Boehler, Carsten N.; Song, Allen W.; Woldorff, Marty G. (Frontiers in Human Neuroscience, 2010)
Being able to effectively explore our visual world is of fundamental importance, and it has been suggested that the straight-ahead gaze (primary position) might play a special role in this context. We employed fMRI in humans to investigate how neural activity might be modulated for saccades relative to this putative default position. Using an endogenous cueing paradigm, saccade direction and orbital starting position were systematically manipulated, resulting in saccades towards primary position (centripetal) and away from primary position (centrifugal) that were matched in amplitude, directional predictability, as well as orbital starting position. In accord with earlier research, we found that fMRI activity in the superior colliculus (SC), as well as in the frontal eye fields (FEF) and the intraparietal sulcus (IPS), was enhanced contralateral to saccade direction across all saccade conditions. Furthermore, the SC exhibited a relative activity decrease during re-centering relative to centrifugal saccades, a pattern that was paralleled by faster saccadic reaction times. In contrast, activity within the cortical eye fields was not significantly modulated during re-centering saccades as compared to other saccade types, suggesting that the re-centering bias is predominantly implemented at a subcortical rather than cortical processing stage. Such a modulation might reflect a special coding bias facilitating the return of gaze to a default position in the gaze space in which retinotopic and egocentric reference frames are aligned and from which the visual world can be effectively explored.